Loujain dreams of sunflowers - AlHathloul, Lina; Mishra-Newbery, Uma (Minedition, 2022)
"Loujain watches her beloved baba attach his feather wings and fly each morning, but her own dreams of flying face a big obstacle: only boys, not girls, are allowed to fly in her country. Yet despite the taunts of her classmates, she is determined to do it--especially because Loujain loves colors, and only by flying can she see the color-filled field of sunflowers her baba has told her about. Eventually, he agrees to teach her, and Loujain's impossible dream becomes reality--and soon other girls dare to learn to fly."--Publisher's website.